Endometrial Metaplastic/Reactive Changes Coexistent with Endometrial Hyperplasia and Carcinoma: A Morphological and Immunohistochemical Study - Antonio Travaglino; Frediano Inzani; Angela Santoro; Damiano Arciuolo; Alessia Piermattei; Sandra Pasquini; Giulia Scaglione; Nicoletta D’Alessandris; Michele Valente; Antonio Raffone; Francesco Fanfani; Gian Franco Zannoni (Diagnostics, 2021)
The aim of this study was to assess the relationship between endometrial metaplastic/reactive changes (EMRCs) and endometrial neoplastic lesions. Twenty cases of “simple” (without architecture complexity) EMRCs coexistent with endometrial malignant/premalignant lesions, twenty cases of neoplasia-unassociated EMRCs, and eight cases of complex metaplastic lesions were assessed by immunohistochemistry. EMRCs coexisted with endometrioid carcinoma (n = 12), atypical endometrial hyperplasia (n = 3), serous carcinoma (n = 2), and clear cell carcinoma (n = 3). Neoplasia-associated EMRCs showed a mean Ki67 labeling index of 12.6% (range 0–30%); with nuclear atypia in 16/20 (80%) cases; diffuse p16 expression in 15/20 (75%) cases; and heterogeneous ER, PR, and vimentin expression. Compared to the associated neoplasia, EMRCs showed a lower Ki67 expression (p < 0.001) and higher p16 expression (p < 0.001). No EMRC case showed mitotic activity, PTEN loss, MMR deficiency, nuclear β-catenin, p53-mutant pattern, Napsin A, or AMACR expression. No significant differences were found between neoplasia-associated and neoplasia-unassociated EMRCs. Complex metaplastic lesions showed a lower Ki67 expression than EMRCs (p = 0.044) and PTEN loss in 5/8 cases, even in the absence of nuclear atypia. In conclusion, neoplasia-associated simple EMRCs may show evident atypia and a worrisome immunophenotype, but no data support their involvement in endometrial carcinogenesis. Architectural complexity appears as a crucial factor to identify precancerous lesions.